2013
DOI: 10.12748/uujms.201324253
|View full text |Cite
|
Sign up to set email alerts
|

Water absorption characteristics of polyester matrix composites reinforced with oil palm ash and oil palm fibre

Abstract: The water absorption characteristics of polyester matrix hybrid composites reinforced with oil palm ash and oil palm fiber have been investigated. Open moulding method was used to produce polyester hybrid composites of 2, 4, and 6 wt% reinforcement consisting of oil palm ash (OPA) and oil palm fiber (OPF) in weight ratios of 1:0, 3:1, 1:1, 1:3 and 0:1 respectively. Water immersion test was used to study the adsorption behaviour from which the water diffusion mechanisms of the composites were established. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 21 publications
(21 reference statements)
0
11
0
Order By: Relevance
“…The main three types of diffusion behaviour were seen in case of CFPCs, as depicted in Table 1 [8,33,42,53,55]. To identify the types of diffusion by analyzing the intercepts and slope of water absorption curve plotted using the following relations [33,53]:…”
Section: Kinetics Of Water Absorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main three types of diffusion behaviour were seen in case of CFPCs, as depicted in Table 1 [8,33,42,53,55]. To identify the types of diffusion by analyzing the intercepts and slope of water absorption curve plotted using the following relations [33,53]:…”
Section: Kinetics Of Water Absorptionmentioning
confidence: 99%
“…In the current decade, the usage of cellulosic fibres as reinforcement in polymer composites for producing low-cost engineering materials with lower environmental impact has gained a great deal of attention [4,5]. These cellulosic fibres offer many advantages such as availability in large amounts, lightweight, high specific strength and modulus, non-health hazards, biodegradable, high specific strengths and modulus, low cost and density, reduced tool wear and enhanced energy recovery [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Water Absorption Test. Water absorption test was carried out in accordance with ASTM D570 [26]. Specimens obtained from tensile tests were placed in an oven at 65°C for 2 days.…”
Section: Determination Of the Mechanical Properties Ofmentioning
confidence: 99%
“…For RPUFs to progressively suit different application requirements for various industries in the future, there is the need to improve the mechanical and thermal properties of the foams while also drastically reducing their health [8] and environmental impact in terms of waste and toxicity [9][10][11]. Different studies have shown that the properties of RPUFs can be enhanced significantly by the use of different filler materials added in a specified proportion [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%